English Language Teachers' Resource Centre: A Model for Developing Contexts - Giri, Ram Ashish (Journal of NELTA, 2011)
It is an irony that when the importance and demand of the English language in the developed as well as developing countries have increased several folds in the last five decades, the standards of its teaching and learning have decreased considerably. The deterioration of standards has been attributed to inadequate English language teaching (ELT) policy, poor teaching environment, inadequate infrastructure, or to ELT practitioners who in most countries are largely untrained. In order to address the problem, the respective countries have been engaged in modernising and improving their curricular practices and teacher preparation programmes for some time now. What is rarely considered is the fact that a good teaching programme requires adequate teaching resources. Central to the amelioration of English language teaching process is unarguably the resource that is available to support the teaching and learning processes. While it is necessary that the teachers are adequately trained, establishment of an English language teachers” resource centre to cater to the developing needs of the teachers (and learners)is essential. This article provides a rationale for the establishment of a teachers' resource centre, and, based on the experience in Nepal, suggests a model for its development and operation in other developing contexts. It discusses features as well as constraints of such a centre, and outlines ways in which it can, despite the constraints, be sustainable. Key words: English language teaching; ELT resource centre; Resource centre facility; Resource centre management; English language teachers Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 64-76 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4611